2013
DOI: 10.5114/ceji.2013.35201
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of the ocular surface and contact lens wear: theoretical fundamentals

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Actually, the tear film, cornea, palpebral and bulbar conjunctiva, main and accessory lacrimal glands, Meibomian glands, as well as eyelids and eyelashes with the associated glands, which constitute the structural and functional components of the ocular surface, show a characteristic immune profile [ 4 – 6 ]. It was also shown that the immunomodulation of this response is possible, which helps avoiding a potential detrimental effect of the excessive response or persistent immune activation [ 5 7 ]. It is essential as the two partly opposing roles of the immune protection include destroying the invading pathogens and limiting the inflammatory response, which may damage delicate ocular structures at the same time [ 8 ].…”
Section: Anatomy and Physiology Of Ocular Surfacementioning
confidence: 99%
“…Actually, the tear film, cornea, palpebral and bulbar conjunctiva, main and accessory lacrimal glands, Meibomian glands, as well as eyelids and eyelashes with the associated glands, which constitute the structural and functional components of the ocular surface, show a characteristic immune profile [ 4 – 6 ]. It was also shown that the immunomodulation of this response is possible, which helps avoiding a potential detrimental effect of the excessive response or persistent immune activation [ 5 7 ]. It is essential as the two partly opposing roles of the immune protection include destroying the invading pathogens and limiting the inflammatory response, which may damage delicate ocular structures at the same time [ 8 ].…”
Section: Anatomy and Physiology Of Ocular Surfacementioning
confidence: 99%
“…Tears lubricate and smooth the ocular surface and the components of the tear film work to trap debris (mucins), kill pathogens (lysozymes, phospholipase, etc. ), facilitate the aggregation of the neutralized foreign bodies (sIgA), and assist with the removal of said bodies through blinking 16…”
Section: Introduction: the Barriers To Topical Ocular Drug Deliverymentioning
confidence: 99%
“…Mucins act to promote an optimally lubricated ocular surface by supporting the spreading of the bulk of the tear film over the corneal and conjunctival tissues. In particular, secreted, gel‐forming MUC5AC and cell adhesive MUC1 facilitate pathogen removal by trapping the pathogen and preventing its adhesion to the underlying epithelial tissue 16b,19. The longer, surface adhesive mucins also allow for the formation of reservoirs of oxidative enzymes, defensins, lysozymes, and lactoferrin—proteins produced by scavenger cells, neutrophilic granulocytes, that are attracted to inflammation—which work to reduce the adhesion of bacteria and remove damaged host tissue 16b,20.…”
Section: Introduction: the Barriers To Topical Ocular Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations